2003
DOI: 10.1161/01.cir.0000056767.69054.b3
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Patients With Chronic Obstructive Pulmonary Disease at Increased Risk of Cardiovascular Diseases?

Abstract: Background-Chronic obstructive pulmonary disease (COPD) increases the risk of cardiovascular disease 2-to 3-fold.The factors responsible for this association remain largely unknown. Methods and Results-We analyzed data from participants, Ն50 years of age, of the Third National Health and Nutrition Examination Survey (nϭ6629) to determine whether C-reactive protein (CRP) and other systemic inflammatory markers are present in participants with chronic airflow obstruction and are associated with cardiac injury. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
367
2
27

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 958 publications
(430 citation statements)
references
References 32 publications
17
367
2
27
Order By: Relevance
“…The direct relationship between chronic lung disease such as emphysema and the incidence of CVD has been known for many years (8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…The direct relationship between chronic lung disease such as emphysema and the incidence of CVD has been known for many years (8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Also, data in a clinical population with visual scores showed that airway wall thickening is associated with future cardiovascular events [33]. Similar to CVD, COPD, emphysema and bronchiolitis are accompanied by low-grade systemic inflammation [8,11,34]. There is growing evidence indicating that cardiovascular disease is a major cause of death in COPD patients [35].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, smoking is considered the most important modifiable risk factor for developing chronic obstructive pulmonary disease (COPD) [8][9][10]. COPD is thought to be an independent risk factor for cardiovascular events [11]. The pathologic features of COPD are destruction of lung parenchyma (emphysema) and inflammation of the small airways (bronchiolitis).…”
Section: Introductionmentioning
confidence: 99%
“…Such a hypothesis is based on the fact that patients with COPD have higher elevation of inflammatory markers [56,57] , and it fits the clinical observation of a higher incidence of troponin elevation [56] and left ventricular wall motion abnormalities [58] noted in patients with COPD and left ventricular dysfunction. Patients with HF and concomitant COPD have higher activation of neurohormones, particularly norepinephrine and plasma rennin [56] .…”
Section: Chronic Obstructive Pulmonary Disease and Heart Failurementioning
confidence: 92%